Extending Automotive SPICE 3.0 for the use in ADAS and future self‐driving service architectures. Issue 5 (12th March 2018) - Messnarz, Richard; Kreiner, Christian; Macher, Georg; Walker, Alastair
Abstract: The SOQRATES (www.soqrates.de ) working party has been established in 2003 with the support of the Bavarian SW initiative. Major automotive suppliers joined forces to exchange best practices in topics such as Automotive SPICE, functional safety, and cybersecurity. The research method of SOQRATES is to compare the best practices, and in case that a specific design pattern is accepted by all parties, it is declared and published as a state of the art. Some of the results of the working party have been packaged into training courses. For example, in the EU project SafEUr (518632‐LLP‐1‐2011‐1‐AT‐LEONARDO‐LMP, 2011‐2012) a European partnership with inputs from SOQRATES developed a skill set, training materials, and best practices for the implementation of ISO 26262. For example, in the EU project AQUA (Knowledge Alliance for Quality in Automotive, EAC‐2012‐0635, 2013‐ 2014), a European partnership with inputs from SOQRATES developed a skill set, training materials, and best practices for integrating Automotive SPICE, ISO 26262, and Six Sigma. For example, in the EU project AQU (Automotive Quality Universities, 2015‐1‐CZ01‐KA203‐013986, 2015‐ 2017), a European partnership with inputs from SOQRATES applied the AQUA concept with universities in Austria, Germany, France, and Czech Republic who educate students that will work in the automotive industry. Also, the working party elaborated integrated assessment models where the Automotive SPICE 3.0 has been merged with ISO 26262 (further safety related questions) and SAE J3061 (further cybersecurity questions). This paper will look into the future of self‐driving cars and discuss the design patterns that are currently analysed in the working party to support a vehicle in future self‐driving infrastructure architectures and processes. Abstract :